2022
DOI: 10.58996/hmj.v5i1.40
|View full text |Cite
|
Sign up to set email alerts
|

Pengujian Potensi Aktivitas Antibakteri dari Daun Cep-cepan (Saurauia cauliflora DC.) dalam Formulasi Sediaan Gel Terhadap Propionibacterium acnes

Abstract: One of the causes of acne is due to a bacterial infection such as Propionibacterium acnes during adolescent puberty. Empirical studies of secondary metabolites contained in Cep-cepan leaves have potential as promising antimicrobials. The main objective of this study was to determine the antibacterial activity of the ethanolic extract of Cep-cepan leaves formulated into a gel preparation against the bacteria Propionibacterium acnes that causes acne. This research method was carried out experimentally where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Jerawat adalah salah satu masalah yang dapat mengganggu keindahan kulit dan mengurangi rasa percaya diri seseorang (Amalyuri et al, 2022) Salah satu faktor yang dapat menyebabkan jerawat adalah bakteri Propionibacterium acne dan bakteri Staphylococcus epidermidis (Syahputra et al, 2022). Saat ini banyak sudah dikembangkan berbagai macam teknologi untuk mengatasi jerawat seperti penggunaan sediaan topical dengan bahan dasar kimiawi, penyinaran dengan sinar UV yang sudah pasti dapat menimbulkan efek samping yang tidak baik untuk kulit, salah satu efek sederhananya adalah mengiritasi kulit atau dapat mengganggu pertumbuhan sel kulit baru (Aliah et al, 2019).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Jerawat adalah salah satu masalah yang dapat mengganggu keindahan kulit dan mengurangi rasa percaya diri seseorang (Amalyuri et al, 2022) Salah satu faktor yang dapat menyebabkan jerawat adalah bakteri Propionibacterium acne dan bakteri Staphylococcus epidermidis (Syahputra et al, 2022). Saat ini banyak sudah dikembangkan berbagai macam teknologi untuk mengatasi jerawat seperti penggunaan sediaan topical dengan bahan dasar kimiawi, penyinaran dengan sinar UV yang sudah pasti dapat menimbulkan efek samping yang tidak baik untuk kulit, salah satu efek sederhananya adalah mengiritasi kulit atau dapat mengganggu pertumbuhan sel kulit baru (Aliah et al, 2019).…”
Section: Pendahuluanunclassified
“…Hal ini membuat sitoplasma sel bocor, sehingga menyebabkan kematian sel. Antimikroba yang membunuh bakteri disebut bakterisida, dan mereka membunuh bakteri dengan cara memecahkan membran sitoplasma (Afrose et al, 2010;Syahputra et al, 2022). Steroid antibakteri yang berhubungan dengan membran lipid, dan kepekaan terhadap komponen steroid yang bisa membuat kebocoran pada liposom.…”
Section: Tabel 3 Kategori Diameter Zona Hambat Bakteriunclassified
“…By spreading the sample on a slide, bonding it with a slide or other clear material, and checking to see if the preparation base was smooth and the surface even, the homogeneity test was conducted. There cannot be any visible coarse granules, and the preparation must display a homogenous pattern [7].…”
Section: Homogenity Testmentioning
confidence: 99%
“…The use of hand sanitizer is a preparation that is currently chosen by many people to keep hands hygienic because it is easy to carry everywhere, and how to use it is also not difficult. Just spraying or pouring the preparation into the palm of the hand and rubbing until all the preparation is evenly distributed to the surface of the hand [5], [6].Gel preparations are used by the public because they have good aesthetic value, are transparent, are easy to spread evenly when applied to the skin without pressure, give a cold sensation, do not cause scars on the skin, and are easy to use [7]. Hand sanitizer gel is a hand sanitizer that contains an active ingredient of 60% alcohol with active ingredients that can use active ingredients derived from nature that have antibacterial activity [8].One of the plants that is efficacious as an antibacterial is the extract of the Temu Hitam rhizome.…”
Section: Introductionmentioning
confidence: 99%
“…Based on research conducted by Syahputra et al, (2022) It was found that the content of flavanoids, alkaloids, triterpenoids, anthraquinone glycosides and tannins in the leaves of Cep cepan (Saurauia cauliflora DC.) had antifungal activity against candida albicans and microsporum canis fungi.…”
Section: Introductionmentioning
confidence: 99%